Respuesta :
Answer:
[tex]4(3 + c) + c = 4 + c \\ 12 + 4c + c = 4 + c \\ 12 + 5c = 4 + c \\ 12 - 4 = c - 5c \\ \\ 8 = - 4c \\ c = \frac{ - 8}{4} \\ c = - 2 \\ thank \: you[/tex]
Answer: c = -2
Step-by-step explanation:
Given
4 (3 + c) + c = c + 4
Expand parentheses and apply the distributive property
4 · 3 + 4 · c + c = c + 4
12 + 4c + c = c + 4
Combine like terms
12 + (4c + c) = c + 4
12 + 5c = c + 4
Subtract 12 on both sides
12 + 5c - 12 = c + 4 - 12
5c = c - 8
Subtract c on both sides
5c - c = c - 8 - c
4c = -8
Divide 4 on both sides
4c / 4 = -8 / 4
[tex]\boxed{c=-2}[/tex]
Hope this helps!! :)
Please let me know if you have any questions